2020
DOI: 10.14740/jocmr4278
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Cardiac Function Following Three-Month Administration of Tofogliflozin in Patients With Diabetes Mellitus

Abstract: Background: Patients with type 2 diabetes mellitus (T2DM) are at increased risk for impairment in heart failure and diastolic relaxation while preserving ejection fraction (EF). Recently, several sodium glucose cotransporter-2 (SGLT2) inhibitors have demonstrated to decrease cardiovascular disease (CVD) events in elderly diabetic patients, although gender difference in the effect of SGLT2 inhibitors is unknown. The objective of the present study was to evaluate gender difference in the effect of tofogliflozin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
(60 reference statements)
1
3
0
Order By: Relevance
“…Third, other residual confounding factors, such as genetics, physical activity or dietary factors, are also not included in the NHI data. However, our results are consistent with those of previous validation studies [ 19 , 20 ]. Fourth, Three types of SGLT2i (Empagliflozin, Dapagliflozin, and Canagliflozin) were launched since May 2016 and used till the end of the study (December 31, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Third, other residual confounding factors, such as genetics, physical activity or dietary factors, are also not included in the NHI data. However, our results are consistent with those of previous validation studies [ 19 , 20 ]. Fourth, Three types of SGLT2i (Empagliflozin, Dapagliflozin, and Canagliflozin) were launched since May 2016 and used till the end of the study (December 31, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, our previous data presented no change in IVCmax (inferior vena cava maximal diameter), [ 13 ] indicating that there is no change in the volume of the vessel, that is, no intravascular dehydration. [ 28 ] Furthermore, we observed no changes in intracellular and extracellular body fluids.…”
Section: Discussionmentioning
confidence: 95%
“…Herein, we performed a retrospective study to investigate the effect of tofogliflozin, an SGLT2 inhibitor, on the HPA system in elderly patients with T2DM. This study included elderly patients diagnosed with T2DM at the Kanazawa Medical University Himi Municipal Hospital from April 2017 to March 2019, as described previously [11–13] . Briefly, elderly patients aged ≥65 years received a single 20 mg dose of tofogliflozin daily for 3 months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] Soga et al [12] reported that dapagliflozin improved atrial volume index (LAVI), left ventricular mass index (LVMI), and E/e' in a few days and maintained it up to 3 months. Higashikawa et al, [13,14] Tochiya et al, [15] and Otagaki et al, [16] reported that tofogliflozin also improved E/e'. A meta-analysis also reported improvement in EF, E/e', and global longitudinal strain (GLS) as class effects of SGLT2 inhibitors.…”
Section: Introductionmentioning
confidence: 98%